2014
DOI: 10.1177/1049731514543023
|View full text |Cite
|
Sign up to set email alerts
|

Adapting Parent–Child Interaction Therapy to Foster Care

Abstract: Objective: This study presents outcomes from a randomized trial of a novel Parent-Child Interaction Therapy (PCIT) model for foster families. Differential effects of two intervention doses on child externalizing and internalizing symptoms are examined. Method: A sample of 102 foster children was assigned to one of three conditions-brief PCIT, extended PCIT, or wait-list control. The brief and extended groups received 2 days of PCIT training and 8 weeks of telephone consultation. The extended PCIT group receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 55 publications
1
55
0
Order By: Relevance
“…This study expands our previous results that indicated both the brief and extended models of PCIT were associated with a significant reduction in child externalizing and internalizing symptoms (Mersky, Topitzes, Grant-Savela, Brondino, & McNeil, 2014). In the present study, we assessed intervention impacts on indicators of parenting stress and behavior, guided by three research questions:…”
supporting
confidence: 87%
See 1 more Smart Citation
“…This study expands our previous results that indicated both the brief and extended models of PCIT were associated with a significant reduction in child externalizing and internalizing symptoms (Mersky, Topitzes, Grant-Savela, Brondino, & McNeil, 2014). In the present study, we assessed intervention impacts on indicators of parenting stress and behavior, guided by three research questions:…”
supporting
confidence: 87%
“…Tests of interactions were conducted between contrast-coded vectors designating the treatment comparisons and linear and quadratic orthogonal polynomial trend contrasts representing time (Mersky et al, 2014). The DPICS-II scores consisted of observational counts, and therefore, a mixed-effects generalized linear model was used to analyze the nonlinear outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…Two of these interventions (PCIT & TF-CBT) were also evaluated in non-adapted forms. The adaptation of PCIT was substantial (see Mersky, Topitzes, Grant-Savela, Brondino & McNeil, 2014 for more details), yet was rigorously tested through a randomized design. The adaptations to IY and TF-CBT were arguably more minor, while also rigorously tested using randomization.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies of PCIT with children with histories of maltreatment have focused on biological parents (Chaffin et al, 2004; Chaffin, Funderburk, Bard,Valle, & Gurwitch, 2011) or traditional foster caregivers (McNeil, Herschell, Gurwitch, & Clemens-Mowrer, 2005; Mersky, Topitzes, Grant-Savela, Brondino, & McNeil, 2014; Mersky, Topitzes, Janczewski, & McNeil, 2015) using full-protocol PCIT. A randomized trial of PCIT as a foster parent training model for non-kinship foster parents caring for children with externalizing behavior problems in the clinical range demonstrated improvement in both child externalizing and internalizing child symptoms (Mersky et al, 2014) as well as caregiver parenting stress (Mersky et al, 2015).…”
Section: Child Directed Interaction Trainingmentioning
confidence: 99%
“…A randomized trial of PCIT as a foster parent training model for non-kinship foster parents caring for children with externalizing behavior problems in the clinical range demonstrated improvement in both child externalizing and internalizing child symptoms (Mersky et al, 2014) as well as caregiver parenting stress (Mersky et al, 2015). However, kinship caregivers were intentionally excluded from these studies.…”
Section: Child Directed Interaction Trainingmentioning
confidence: 99%